Pengaruh Perbedaan Komposisi Silase Berbahan Pelepah dan Bungkil Inti Sawit (Elaeis Guineensis) Terhadap Kualitas Fraksi Serat - Anwar Efendi Harahap; Rahmi Febriyanti; Iman Zainuddin Daulay; Bakhendri Solfan (Universitas Islam Kadiri, 2021)
Silage is a feed technology that aims to ensure the availability of ruminant animal feed, especially during the dry season, silage products can be obtained from oil palm plantation waste in the form of leaves and palm kernel cake. This study aims to the content of the silage fiber fraction of palm leaves and palm kernel cake which are used as silage feed so that they have the potential as animal feed. The parameters of this research are the content of neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent ligni (ADL), sesulose and hemicellulose The study used a completely randomized design (CRD) with 4 treatments and 4 replication, A0: 100% palm leaves + 0 % palm kernel cake; A1: 60% palm leaves + 40% palm kernel cake; A2: 50% palm leaves + 50% palm kernel cake; A3: 40% palm leaves + 60% palm kernel cake. The result showed the higher the gived of palm kernel cake has a very significant effect (P <0.01) reducing the content of neutral detergent fiber (NDF) 69.96% - 57.10%, acid detergent fiber (ADF) 54.99%. - 47.43, acid detergent ligni (ADL) 17.82% -15.09%, Hemicellulose 14.96% - 9.67%, and increase cellulose 25.87% - 28.10%. The concluded the best silage treatment was at 40% palm limb + 60% palm kernel cake because it can reduce the content of NDF, ADF, ADL and increase the content of cellulose